2020
DOI: 10.1098/rsob.200180
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution of single amino acid polymorphisms in Plasmodium vivax Duffy-binding-like domain and implications for vaccine development efforts

Abstract: Plasmodium vivax ( Pv ) malaria continues to be geographically widespread with approximately 15 million worldwide cases annually. Along with other proteins, Duffy-binding proteins (DBPs) are used by plasmodium for RBC invasion and the parasite-encoded receptor binding regions lie in their Duffy-binding-like (DBL) domains—thus making it a prime vaccine candidate. This study explores the sequence diversity in Pv DBL globally, with an emphasis on India a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 87 publications
(218 reference statements)
0
7
0
Order By: Relevance
“…(iv) A strain transcending Pv DBPII-based vaccine demands a globally conserved epitope. Mittal et al , in their global Single Amino Acid Polymorphism (SAAP) data analysis reported that from the four Pv DBL–mAb complex structures, 2 out of the 4 purported neutralizing mAbs do not bind near the supposed dimer interface ( Mittal et al., 2020 ). Such discoveries points towards the fact that a vaccine against P. vivax could have more impact if above challenges of Pv DBPII (as the lone candidate) were considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(iv) A strain transcending Pv DBPII-based vaccine demands a globally conserved epitope. Mittal et al , in their global Single Amino Acid Polymorphism (SAAP) data analysis reported that from the four Pv DBL–mAb complex structures, 2 out of the 4 purported neutralizing mAbs do not bind near the supposed dimer interface ( Mittal et al., 2020 ). Such discoveries points towards the fact that a vaccine against P. vivax could have more impact if above challenges of Pv DBPII (as the lone candidate) were considered.…”
Section: Discussionmentioning
confidence: 99%
“…(2014) . Although these structural and biophysical studies provide deep insight into Pv DBPII-DARC engagement, further studies are required to assess these models as this region is prone to polymorphisms ( Mittal et al., 2020 ) and as a result, the inherent variability in Pv DBL might render the Pv DBP-based vaccines inefficacious. Further, Yogavel et al.…”
Section: Duffy-binding-like Sub-family Of Erythrocyte-binding-like Fa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar concerns are also being addressed for COVID-19 vaccines whose efficacy may be altered against new variants having SNPs (Harvey et al, 2021). Similarly, a recent study on Plasmodium vivax DBL (Duffy-binding like) protein that binds to DARC (Duffy antigen receptor for chemokines) receptor for invasion into red blood cells showed inherent variability in its sequences worldwide, which may act as a limitation for the development of an effective, universal vaccine (Mittal et al, 2020). Thus, it is clear that region-wise or country-wise polymorphism analysis in the ligand-binding domain of VAR2CSA must be covered for vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…Inherent variability in genomic sequences of drug and vaccine targets can be a shortcoming in the design and development of effective therapies as the targets will be naturally resistant (compromised) [ 24 , 25 ]. Any amino acid change, particularly at the active site of a drug target, can induce alterations in the structural features which will alter its interaction with the drug and can lead to weak or no binding.…”
Section: Introductionmentioning
confidence: 99%